Diare pada sapi neonatus yang ditantang Escherichia coli K-99 - Anita Esfandiari; Sus Derthi Widhyari; Ali Hujarat (Institut Pertanian Bogor, 2011)
The objective of this experiment was to study the efficacy- of colostrum given to neonatal calves challenged by Escherichia coli (E. col!) K-99. Ten healthy calves devided into two groups i.e. colostrum group (given colostrum originated from cows vaccinated by E. coli) and non-colostrum group (given whole cow milk). Colostrum or milk were given to the calves at amounts of 10% of body weight directly after birth and Followed by the same amount every 12 h, for three days. Challenged were done orally to all newborn calves when they were 12 hours of ages, using live bacteria of E. coli K-99. Fecal samples were collected every 12 hours for one week. Results of the experiment indicated that all calves experienced diarrhea following challenge tests. However, the non colostrum group showed a frequent defecation, more liquid faeces, a longer length of diarrhea and more severe clinical signs of diarrhea. It was confirmed that E' coli found and every feacal Samples,collected. In conclusion, colostrums collected from cow vaccinated by E. coli showed protective properties against E. coli K-99 infection.